Crimes that shook the world - Discovery Channel (Firm). (United States Discovery Communications, Inc., 2010)
From the Backpack Killer of Australia to the Vienna Strangler, Crimes that Shook the World profiles major crimes of the 21st century with interviews from investigating officers, forensic scientists and the victims' families. By using real police video material, archive news footage and dramatic reconstruction, it tells some of the most world-renown serial killer stories.
Disc 1 (ca. 96 min.). Manson : Most Evil -- Disc 2 (ca. 192 min.). Vienna Strangler / director, Ross Harper ; series producers, Elspeth O'Hare, Kathryn Ross ; executive producer, Alan Clements ; an Eyedoubleyousee production part of the RDF Media Group ; Decoding evil cold blooded killers / executive producer, Beth Hoppe ; producer & field director, Paul Cabana ; director, Shelley Schulze ; executive producer, Julian P. Hobbs ; produced for Discovery Channel by Optomen Productions -- Disc 3 (ca. 192 min.). House of horrors / director, Eleanor Yule ; series producers, Elspeth O'Hare, Kathryn Ross ; executive producer, Alan Clements ; an Eyedoubleyousee production part of the RDF Media Group ; BTK : bind, torture, kill / director, Andy Webb ; narrator, Tim Pigott-Smith ; executive producer, Alan Clements ; an Eyedoubleyousee production part of the RDF Media Group.
Title from container.
Package design and summary by Discovery Communications, LLC.
3 containers in 1 package: VDR-1581 (1 DVD); VDR-1582 (1 DVD); VDR-1583 (1 DVD).
Originally released as a TV Series.
DVD videos.
Keywords: Crime analysis; Nonfiction television programs; Documentary television programs; Serial murderers; Criminals